THE SIGNIFICANCE OF THE BATTLE FOR CUITO CUANAVALE: LONG-TERM FORESIGHT OF THE CURRENT STRATEGIC LANDSCAPE - Velthuizen, Andreas (Scientia Militaria - South African Journal of Military Studies, 2011)
This article deals with the long-term outcomes of the Battle of Cuito Cuanavale in Angola (1987–1988) and the effect of the outcomes on the current strategic landscape in Southern Africa. The crux of the article is to learn about the value of long-term foresight for strategising in an international context. After a short discussion of the research methodology, the desired long-term outcomes, as perceived by the major roleplayers before the battle, will be described and explained. For the purpose of elucidation, a description is included of the events preceding the battle and the course of the battle itself. Finally, the long-term outcomes within the context of the current strategic landscape in Southern Africa will be described and explained. The article concludes with recommendations on the value of long-term strategic foresight and the importance to maintain strategic instruments, including military force, to ensure that the foreseen outcomes become reality.